AIDS and Watersheds: Understanding and Assessing Biostructural Interventions - Loevinsohn, Michael (International Food Policy Research Institute, 2006)
Over the past 15 years, evidence has accumulated of how HIV/AIDS impacts rural people who depend for their food and livelihood on agriculture and the management of natural resources. Evidence is also available, though less extensive, of how changes in the rural environment influence the dynamics of HIV/AIDS. It is striking, however, how little this understanding has yet to contribute to the methods used in the struggle with HIV/AIDS. The “expanded response” that UNAIDS is spearheading to meet the targets set by the UN General Assembly Session on HIV/AIDS in 2001 includes no reference to agricultural or natural resource–based measures for prevention, treatment, and care (Stover et al. 2002). This is hardly surprising because there is as yet little documented evidence of their effectiveness in HIV/AIDS control terms or feasibility on a wide scale. Much less is it clear how such efforts might be financed. Across the sectoral divide, agricultural and natural resource management policies and programs are aimed at enhancing food security, improving nutrition, and expanding livelihood opportunities. However, the decisionmakers responsible for the most part have a very limited understanding of how these may be affecting HIV/AIDS risks, positively or negatively, and how these inadvertent effects can be optimized. Few have a clear understanding of how HIV/ AIDS is affecting or will in the future affect attainment of the objectives they now pursue and what adjustments will be necessary to keep these in sight.